Analisis Error Pembacaan Tegangan DC pada Kondisi Overvoltage dan Undervoltage Menggunakan Input Analog PLC - Adhityo Samola; Arnold Kalalo; Fanny Doringin; Sukandar Sawidin; Muchdar Patabo; Maruto Loegimin (Universitas Muhammadiyah Surabaya, 2026)
Voltage monitoring is an important aspect in electrical systems to maintain operational stability and prevent damage to electrical equipment. In systems based on Programmable Logic Controller (PLC), voltage measurement is carried out through an analog input module that converts analog signals into digital data, which is then processed using a scaling method to obtain the actual voltage value. This conversion process has the potential to produce errors due to the limitations of analog input resolution, noise, and measurement device tolerances. This study aims to analyze the error level of DC voltage readings using PLC analog input under overvoltage and undervoltage conditions. The method used is an experimental approach by comparing the reference voltage from an adjustable power supply with the PLC reading results at several voltage variations. The reference voltage is converted into an actual voltage scale using a linear approach, then analyzed using the percentage error method. The results show that the error value ranges from 0% to 1.38%, with an average value of approximately 0.96%, and the highest error occurs under overvoltage conditions. This indicates that the system has good accuracy with relatively small and stable error levels. Therefore, the PLC-based voltage monitoring system is feasible for voltage monitoring applications with an acceptable level of measurement error.